Furfurylation of tropical wood species with and without silver nanoparticles: Part I: Analysis with confocal laser scanning microscopy and FTIR spectroscopy. Issue 6 (2nd November 2022) - Gaitán-Alvarez, Johanna; Moya, Roger; Mantanis, George I.; Berrocal, Alexander
ABSTRACT: This work focused on the upgrading of non-durable tropical wood species originating from fast-growing plantations of Costa Rica. Modification of such tropical woods with furfuryl alcohol, although has not been broadly studied up to date, offers a potential way to increase their low durability. The purpose of this research was to investigate the modification effects on cell wall, vessels wall, radial and axial parenchyma using confocal laser scanning microscopy (CLSM) as well as the changes in the bands of chemical composition using Fourier-transform infrared spectroscopy (FTIR). In fact, nine tropical wood species such as Cedrela odorata, Cordia alliodora, Enterolobium cyclocarpum, Gmelina arborea, Hieronyma alchorneoides, Samanea saman, Tectona grandis, Vochysia ferruginea and Vochysia guatemalensis were treated with plain furfuryl alcohol (FA), and furfuryl alcohol combined with silver nanoparticles (FA-NPsAg). Furfurylation effects were also assessed by the weight percentage gain (WPG) of wood. Results showed that WPG varied from 14.4% to 44.3% with the FA treatment, and from 12.9% to 44.5% with the FA-NPsAg treatment. In the species which exhibited a WPG over 25% with the FA treatment, fluorescence at 600 nm band occurred mostly in the cell walls of fibres, while the furfurylation degree in radial and axial parenchyma was limited. Moreover, furfurylation occurred in lesser extent in wood species with high abundance of axial parenchyma as revealed by fluorescence. Wood species such as Vochysia ferruginea, Vochysia guatemalensis, Cedrela odorata, Samanea saman, Enterolobium cyclocarpum, which showed WPGs>25%, evidenced considerable changes in the lignin structure as observed in the FTIR spectra. In particular, with the FA treatment, the changes were observed in the bands of 1711, 1652, 1561, 889, 796 and 733 cm –1, whereas, with the FA-NPsAg treatment, the changes occurred in the bands of 1711, 1505, 1426, 1370, 1224 and 1016 cm –1 . Overall, no significant difference was found in FTIR spectra and anatomical fluorescence between the FA and FA-NPsAg treatment, probably because the NPsAg concentration was insufficient for a change to occur in the bonds.